PENGARUH DUKUNGAN ORGANISASI DAN DIGITAL COMPETENCE TERHADAP PELAKSANAAN REKAM MEDIS ELEKTRONIK DENGAN KOMITMEN ORGANISASI SEBAGAI MEDIASI - Kurniawati Kurniawati; Chalimah Chalimah (Jurnal GeoEkonomi, 2024)
The aim of this study to analyze the influence of organizational support, digital competence and organizational commitment as mediation on the implementation of electronic medical records (RME) in hospitals. The sample in this study was 176 people from all users of electronic medical records at RSI PKU Muhammadiyah Pekalongan. Primary data is obtained directly via Google Form. The analysis technique using SEM-PLS. The research results concluded (1) The influence of organizational support is not significant on the implementation of RME; (2) The influence of Digital competence is significant on the implementation of RME; (3) The influence of organizational commitment is significant on the implementation of RME; (4) The influence of organizational support is significant on organizational commitment; (5) The influence of digital competence is significant on organizational commitment; (6) Organizational support has no significant effect on the implementation of RME, mediated by organizational commitment; (7) The influence of digital competence is significant on the implementation of RME, mediated by organizational commitment